Respuesta :

gmany

Answer:

x = 1 and y = -6 → (1, -6)

Step-by-step explanation:

[tex]y=-7x+1\qquad(1)\\\\5x+4y=-19\qquad(2)\\\\\text{Substitute (1) to (2):}\\\\5x+4(-7x+1)=-19\qquad\text{use the distributive property}\\\\5x+(4)(-7x)+(4)(1)=-19\\\\5x-28x+4=-19\qquad\text{subtract 4 from both sides}\\\\5x-28x+4-4=-19-4\qquad\text{combine like terms}\\\\-23x=-23\qquad\text{divide both sides by (-23)}\\\\\dfrac{-23x}{-23}=\dfrac{-23}{-23}\\\\x=1[/tex]

[tex]\text{Substitute the value of}\ x\ \text{to (1):}}\\\\y=-7(1)+1\\\\y=-7+1\\\\y=-6[/tex]

ACCESS MORE